MOTHER'S CHILD FEEDING KNOWLEDGE AND PRACTICES ASSOCIATED WITH UNDERWEIGHT IN CHILDREN UNDER-FIVE YEARS: A STUDY FROM RURAL KONAWE, INDONESIA - Tasnim, Tasnim; Mwanri, Lillian; Dasvarma, Gour (Public Health of Indonesia, 2018)
Backgroud: Many rural mothers did not give appropriate child feeding which impacted to underweight for their children in Konawe Disrict of Southeast Island in Indonesia. This was also related to mother's poor knowledge about child feeding. Objective: this study aimed to investigate the relationship between rural mothers' knowledge and their practices of child feeding with underweight in under-5 children in Konawe District, Southeast Sulawesi Province in Indonesia.Methods: The case-control study was conducted in 5 rural areas in Konawe District, Southeast Sulawesi Province. The study involved 400 under five children and their mothers, including 100 of whom were cases and 300 of whom were age-matched contorls (1:3). Cases were underweight children, while the controls were children with a normal nutritional status. The independent variabels were mother's knowledge and  their child feeding practices. The data analysis used Conditional Logistic regression.Results: poor mothers' knowledge (odds ratio [OR], 8.9; 95% confidene interval [CI], 4.0 to 19.6;  p<0.001), poor practices of under-5 children feeding  (OR, 15.2; 95% CI, 5.5-41.7; p<0.001) significantly associated with underweight in rural children.Conclusion: Mothers' knowledge about the availability of nutritious foods determines her child feeding practices. A mother's level of knowledge about nutritious foods and her practices is related to her educational level and health information sources.